2010
DOI: 10.1111/j.1439-0396.2009.00942.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Effects of ambient temperature and soybean meal supplementation on intake and digestion of two sheep breeds differing in mature size

Abstract: The aim of this study was to compare the intake and digestive physiology of mature ewes of two breeds--Ile-de-France (mature weight: 75-80 kg) and Churra-da-Terra-Quente (CTQ; mature weight: 45-50 kg)--and evaluate the effects of ambient temperature and protein supplementation in the comparison. The temperature (25 °C vs. 11 °C) and soybean meal supplementation (150 g/kg of ingested hay on dry matter basis vs. unsupplemented control) were evaluated in 48 adult ewes of two breeds fed hay ad libitum and at a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…() reported similar results using cattle with weights inserted into the rumen to measure effect of ruminal distension on MRT and MY while Lourenço et al. () recorded no temperature effect on apparent digestibility when exposing two different breeds of sheep to different diets and ambient temperatures. This suggests that exposing animals to low ambient temperatures may cause an improvement in the efficiency of utilisation of dietary energy.…”
Section: Discussionmentioning
confidence: 85%
“…() reported similar results using cattle with weights inserted into the rumen to measure effect of ruminal distension on MRT and MY while Lourenço et al. () recorded no temperature effect on apparent digestibility when exposing two different breeds of sheep to different diets and ambient temperatures. This suggests that exposing animals to low ambient temperatures may cause an improvement in the efficiency of utilisation of dietary energy.…”
Section: Discussionmentioning
confidence: 85%
“…These hormones have thermogenesis capacity and play an important role in certain physiological functions related to growth, reproductive efficiency and dairy production (West 2003;Al-Haidary 2004). The animals exposed to thermal stress conditions can reduce these hormones when the air temperature increases sharply (Todini et al 2007;Helal et al 2010;Lourenço et al 2010;Maurya et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…When the ewes were compared, at the same degree of maturity and given similar levels of feeding, the rate of passage of feed particles was approximately 90% faster in Churra than in Ile‐de‐France (Lourenço et al., ). This result was later confirmed with mature animals and at the same level of intake (Lourenço et al., ). It is not known whether, and to what extent, the same digestive feature, that is, a higher rumen outflow rate, has been developed by Barrosão cattle, whose female mature weight is also approximately 60% of its Holstein–Friesian breed counterpart.…”
Section: Resultsmentioning
confidence: 53%
“…Previous comparisons made in our laboratory with growing and mature sheep fed mixed diets and cereal straw or hay supplemented with a protein source, showed that the ability to digest fibre was also higher in the improved Ile‐de‐France breed than in the native Churra breed (Lourenço et al., , ; Gomes, ). These two breeds differ largely in mature weight, with the LW of the Churra breed being approximately 60% of that of the Ile‐de‐France one.…”
Section: Resultsmentioning
confidence: 83%